Cause Marketing Effectiveness and the Moderating Role of Price Discounts. (November 2014) - Andrews, Michelle; Luo, Xueming; Fang, Zheng; Aspara, Jaakko
Can cause marketing (CM) be effective? If so, do price discounts moderate CM effectiveness? Despite the prevalence of linking product sales with donations to charity, field evidence of CM effectiveness is lacking. This is of particular concern for managers who wonder whether the findings of laboratory experiments extend to actual consumer purchases. Using large-scale randomized field experiments with more than 17, 000 consumers, this research documents that CM can significantly increase consumer purchases. Notably, the answer to the second question is more complicated. Under the moderating role of price discounts, the impact of CM on sales purchases may follow an inverted U-shaped relationship—that is, strongest when price discounts are moderate rather than deep or absent. Follow-up lab experiments reveal that consumers' warm-glow good feelings from CM represent the underlying process. These findings provide novel insights into the boundary conditions and mechanisms of the sales impact of CM for researchers and managers alike.